A MEMS-based guidance, navigation, and control unit - Soehren, W.; Schipper, B.; Lund, C. (IEEE Position, Location and Navigation Symposium 2001, 2002)
Honeywell Laboratories, in conjunction with Honeywell Sensor and Guidance Products (SGP) operation, has developed a next generation guidance, navigation, and control unit based on MEMS sensor technology occupying less than 25 in./sup 3/. This product, known as the micro Flight Management Unit (/spl mu/FMU), has applicability across a wide variety of military and commercial applications, including low cost military gun hardened projectiles, personal navigation systems, and commercial AHRS. When coupled with Honeywell's second generation C++-based Embedded Computer Toolbox and Operating System (ECTOS/sup TM/ IIc), the /spl mu/FMU can be utilized easily and effectively for rapid prototyping demonstrations (including customer generated guidance and control software), as well as full production systems. Utilizing a Motorola PPC745 (G3) processor, the /spl mu/FMU has been designed to accommodate next generation GPS/INS ultra-tightly coupled integration algorithms. The /spl mu/FMU electronics have been high G tested to 6,300 Gs (non-operating), successfully demonstrating that the hardware survives and operates after exposure to high G shock. This paper presents an overview of the /spl mu/FMU and ECTOS/sup TM/ IIc software. The hardware architecture and technical specifications of the /spl mu/FMU will be presented, along with the process used to validate the /spl mu/FMU's high G survivability. The software architecture, capabilities, and customer usability /programmability features of ECTOSTM IIc will also be described.